Formation conditions of various calcite types and unusual alteration products of wollastonite in calcite marble near Nezdice (Varied Group of Moldanubicum), Czech Republic - Zak,K.; Dobes,P.; Vrana,S. (Journal of the Czech Geological Society, 1997)
Extensive calcite-rich replacements after wollastonite have been found in an abandoned marble quarry near Nezdice, Sumava Mts., southern Czech Republic. Because any natural reversals of wollastonite reaction both in high-temperature and low-temperature environment are rare, combined mineralogical and stable isotope study of these pseudomorphs was performed. Other types of calcite observed in the quarry include marble in the zones of metamorphic decarbonation, hydrothermal vein calcite and calcite related to karstification process. Stable isotope and fluid inclusion methods were used to study the other types of calcite for comparison purposes. A plausible scenario of the formation of the calcite pseudomorphs involves the following two step evolution mode: (1) transformation of wollastonite to optically and X-ray amorphose phase (which could probably result from a high-rate tectonic deformation or shock wave compression), (2) reaction of the relatively unstable amorphose phase with water having high contents of CO2 to CaCO3, mainly in the zone of supergene alteration. Formation of the secondary carbonates during weathering is strongly indicated by oxygen and carbon isotope composition. The carbonate-rich pseudomorphs after wollastonite still contain relics of the optically and X-ray amorphose phase which formed by transformation of wollastonite and retains its accicular crystal shape. Alternative modes of formation of the pseudomorphs, including, e.g., a spontaneous decomposition of wollastonite to CaO + SiO2 (due to shock wave deformation) during the step (1) or high-temperature reaction of a part of wollastonite with calcite (from the enclosing marble) to larnite, spurrite, or other very high-temperature minerals (also an alternative of step 1) could not be supported by observation; no remains of CaO or larnite were observed. Such unstable high-temparature minerals formed from wollastonite would transform to CaCO3-rich pseudomorphs on exposure to water having a high content of CO2. Formation of the pseudomorphs by incongruent dissolution of wollastonite in the zone of weathering is not supported by observation - wollastonite behaviour as a stable mineral during weathering is well known. Associated diopside, quartz, and primary calcite show no replacement by secondary calcite. Stable isotope analyses and fluid inclusion study of calcite crystals coating some open fractures in the marble quarry indicate that this hydrothermal acivity has no connection with formation of the pseudomorphs after wollastonite.
Keywords: wollastonite; calcite-rich pseudomorphs after wollastonite; oxygen and carbon isotopes in calcite; fluid inclusions; deformation of marble; Moldanubian Zone